Temporary Trade - Balázs Muraközy; Gábor Békés (Hungarian Academy of Sciences, Institute of Economics, 2009)
Most trade theories assume bilateral trade relationships are forged on the basis of some comparative advantages, scale considerations, market structure or some productivity advantage of firms. Since these factors change slowly, bilateral trade relationships should be stable. However, we argue that over half of the non-zero bilateral trade relationships are of temporary nature: they last for a short period only or appear and disappear in an erratic fashion. With a very detailed country-product transaction level dataset on Hungarian exports, evidence is provided for the importance of temporary trade relationships at the bilateral level. A large share of bilateral trade flows are driven by just a few firms, and results indicate that temporary trade is important for all kinds of firms and products. In terms of empirical applications, we show that gravity equations suggest important differences between the determinants of permanent and temporary trade; and the extensive and intensive margins of trade can also be very sensitive to changes in temporary trade.
Keywords: F12; F14; D21; D24; 330; international trade; duration of trade; firm-product level data; Internationale Wirtschaftsbeziehungen; Dauer; Ungarn